(untitled) (International journal of artificial intelligence, 2026)
The article explores current trends and methodological principles of teaching Russian as a foreign language (RFL) in academic lyceums of the Republic of Uzbekistan. The study analyzes the goals and objectives of RFL instruction, the specific characteristics of the learner population, and modern pedagogical approaches aimed at developing communicative, academic, and sociocultural competence. Particular emphasis is placed on the integration of linguistic and cultural components, the application of interactive and digital teaching technologies, and the use of interdisciplinary connections to support the academic orientation of language education. The findings indicate that effective RFL instruction in academic lyceums requires a comprehensive and differentiated approach that takes into account learners’ age, cognitive development, and motivational factors.